Hubungan Fungsi Keluarga dengan Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Kartasura - Husaini, Wilda, dr. Yusuf Alam Romadhon, M.Kes (2017)
The Correlation Of Family Funcion With Exclusive Breastfeeding In Working Area Of Puskesmas Kartasura: (1) The main indicators of public healt level including the infant mortality rate (imr). Imr does not stand alone, butrather related to many factor, one of wich is a nutritional factor. The most perfect nutrition for infants are exclusively breastfed for the first 6 mont of life. Exclusive breastfeeding is proven to reduce the risk of infant mortality rate (imr) and morbidity of acute and chronic disease, because breast milk containts nutrients and antibodies that are good for the baby. (2) This study aimed to anlyze the ralationship between family function with exclusive breastfeeding in puskesmas kartasura. (3) This study used an observational analytic method with cross sectional approach, using cluster random sampling. The number of samples were 66 mothers with toddlers 7-24 months of age who are in posyandu puskesmas kartasura sukoharjo district. The data were obtained from questionnaire which analyzed by chi square test. (4) In the 66 respondents with unhealty family functioning, there were 4 (6.1%) who exclusive breastfed. While on respondents with ahealty family function there were 35 (53.0%) with exclusive breastfeeding. Based on the result of chi square test to determine the relationship of family function with values obtainedexclusive breasfeeding significancy 0.002 or p value < 0.05. (5) Based on this results, then there is a significant relationship between family function with exclusive breastfeeding.